The Palgrave Handbook of Peace, Conflict and Security Studies in Africa
XXI, 497 p. 8 illus.
Keywords: The Palgrave Handbook of Peace, Conflict and Security in Africa is a groundbreaking reference resource that offers an interdisciplinary and decolonial exploration of peace, conflict, and security across the African continent. It features theoretical articulations that explore new approaches to peacebuilding in Africa, rethinking peacebuilding strategies and decolonized approaches to governance and peace sustainability. The volume is organized into three thematic sections—Peace, Conflict, and Security—each addressing the theoretical foundations, methodological innovations, and emerging challenges that shape Africa’s unique peace and security landscape. The chapters provide both theoretical and methodological insights while highlighting locally grounded strategies and alternatives to dominant Western frameworks. Dr. Elias Omondi Opongo, (lead editor) is an associate professor of peace studies and international relations, and Director at the Centre for Research Training and Publications, Hekima University College, Kenya Dr. David Kaulem is the Dean of the School of Education and Leadership at Arrupe Jesuit University in Harare, Zimbabwe Professor Susan Kilonzo is a Lecturer in the Department of Religion and Sociology at Maseno University, Kenya Dr. Sarah Njeri is a Lecturer in the Department of Humanitarianism and Development, School of Oriental and African Studies (SOAS), University of London, UK.